1987
DOI: 10.1002/ajim.4700110207
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey of kidney function in refinery employees

Abstract: We examined sensitive biochemical and immunological markers of kidney function and damage in 53 male oil refinery workers exposed to hydrocarbons and compared their results with those of a control group of 61 age-matched nonexposed males. The mean duration of employment of exposed males was 11 years. The current levels of exposure to a variety of aliphatic and aromatic hydrocarbons, as determined by personal monitoring, were well below the current threshold limit values. No difference was found in the urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The result of this study showed that chronic low level of hydrocarbons exposure does not pose any risk for renal diseases (Viau et al, 1987) (Figure 2). …”
Section: Chronic Exposurementioning
confidence: 78%
See 1 more Smart Citation
“…The result of this study showed that chronic low level of hydrocarbons exposure does not pose any risk for renal diseases (Viau et al, 1987) (Figure 2). …”
Section: Chronic Exposurementioning
confidence: 78%
“…Khan and Yusufi (2009) reported the nephrotoxic effects of benzene by examining 33% increase in blood urea nitrogen (BUN) and 30% increase in serum creatinine in rats exposed to benzene at dose 800 mg/kg for 30 days (Khan and Yusufi, 2009). Viau et al (1987) published a cross sectional study of 53 male oil refinery workers exposed to hydrocarbons including benzene and 61 non-exposed workers.…”
Section: Chronic Exposurementioning
confidence: 99%
“…Viau et al did not find significant effects on kidney function markers of refinery workers who were occupationally exposed to hydrocarbons, the major component of natural or LPG gas [27]. To the best of our knowledge and according to the international available published works, no other studies have been performed to address the effect of LPG or natural gas on kidney function tests.…”
Section: Haematological Parametersmentioning
confidence: 89%
“…In several human studies, prolonged exposure to hydrocarbons has also been found to be associated with a variety of severe glomerular lesions, including mild to severe glomerular nephritis (GN) and Goodpasture's syndrome [110][111][112][113][114][115]. Evidently, hydrocarbon exposure may indeed induce GN and worsen its course, and hence renal function, in many patients [116].…”
Section: Nephrotoxicitymentioning
confidence: 99%